Analysis of Performance Assessment System Model of Civil Servants in Gorontalo Province Training and Education Agency - Djamila Podungge; Imam Mashudi; Karlina Napu (Borong Newinera Publisher, 2020)
This study aims to analyze the Model Apart Civil Servant Performance Assessment System (SIRANSIJA) in the Gorontalo Province Education and Training Agency. This research method uses a survey method with data collection techniques are observation, interview and literature study. The data analysis technique was carried out through the process of data reduction, data presentation and conclusion. The results of this study are the results of this study are the Performance Appraisal System for Civil Service State Apparatus (SIRANSIJA) at the Gorontalo Province Education and Training Agency based on the Governor Regulation (PERGUB) No. 50 of 2016 which is then implemented through the SIRANSIJA application with the indicators being Integrity, Work Ethic and Mutual Cooperation. The implementation of this Assessment System is also regulated by principles that are objective, measurable, accountable, participatory, and transparency. The conclusion in this study is that the implementation of SIRANSIJA based on Gorontalo Governor Regulation Number 50 of 2016 in terms of the discipline of the State Civil Apparatus (ASN) has been effective in optimizing attendance, but in terms of ASN performance, it still needs a lot of improvement.